Perempuan dengan Peran Ganda dalam Rumah Tangga - Junaidi, Junaidi; Sukanti, Nadia Deby (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2022)
This paper explores the Islamic perspective on gender equality, emphasizing the harmonious coexistence of rights and responsibilities between men and women in both private and public spheres. The discussion surrounding the theme of gender within an Islamic framework is extensive, particularly regarding the dual role of women within both domestic and public spheres. In Islamic teachings, the fundamental equality of men and women is emphasized, asserting that both genders share equal humanity, devoid of hierarchical privileges. This equality extends to spiritual essence and societal positioning, as elucidated in the Quran. Within the Islamic context, women are liberated from the sole responsibility of providing for their families, as this duty falls upon the husband, thereby ensuring the equitable distribution of familial obligations. Moreover, Islam permits women to engage in livelihood pursuits within the bounds of Islamic jurisprudence, underscoring a balanced approach to gender roles. AbstrakArtikel ini mengeksplorasi perspektif Islam tentang kesetaraan gender, yang menekankan koeksistensi yang harmonis antara hak dan tanggung jawab antara laki-laki dan perempuan di ranah privat dan publik. Diskusi seputar tema gender dalam kerangka kerja Islam sangat luas, terutama mengenai peran ganda perempuan di ranah domestik dan publik. Dalam ajaran Islam, kesetaraan mendasar antara pria dan wanita ditekankan, dengan menegaskan bahwa kedua jenis kelamin memiliki kemanusiaan yang sama, tanpa hak istimewa hirarkis. Kesetaraan ini mencakup esensi spiritual dan posisi sosial, seperti yang dijelaskan dalam Al-Quran. Dalam konteks Islam, perempuan dibebaskan dari tanggung jawab tunggal untuk menafkahi keluarga mereka, karena tugas ini dibebankan kepada suami, dengan demikian memastikan distribusi kewajiban keluarga yang adil. Selain itu, Islam mengizinkan perempuan untuk terlibat dalam kegiatan mencari nafkah dalam batas-batas yurisprudensi Islam, menggarisbawahi pendekatan yang seimbang terhadap peran gender.